Biodynamic characteristics of maximum speed development - Coh, M.; Babic, V. (Facta Universitatis: Series Physical Education and Sport, 2010)
The purpose of the present review article is to bring together some of the most important findings from the field of maximum speed development from the aspect of biomechanical, motor and neuro-muscular factors. Maximum speed is a complex biomotor ability, which manifests itself in real sports situations and is an important generator of the success of athletes in various sports disciplines. Efficiency of maximum speed is defined in terms of frequency and the length of one's stride. Both parametres are mutually dependent; they also depend on the processes of the central regulation of the motor stereotype. From the biomechanical point of view, a running stride as a basic structural unit depends on the eccentric-concentric muscular cycle of take-off action. Utilisation of elastic strength in the muscular-tendon complex and pre-activation of m. gastrocnemius is highly important in this segment. Maximum speed is a very limited hereditary biomotor ability which is characterized by a reduced possibility for controlling movement. The cerebellum, co-activation of muscles in the kinetic chain and the frequency of activation of motor units play important roles in controlling the activation of agonists and antagonists. The primary goal of training is to create an optimal model of the motor stereotype in the zone of maximum speed. Such a process has to be long-term and methodical.